Peter Bergen, The United States of Jihad: Who Are America’s Homegrown Terrorists and How Do We Stop Them? - Ms. Mehreen Binte Talha (CISS Insight Journal, 2017)
Peter Bergen is a renowned journalist who has authored seven books to date, three of which were New York times bestsellers. He has written extensively on terrorism and is on the editorial board of the “Studies in Conflict & Terrorism”, a leading scholarly journal on the subject of terrorism. The author has also held teaching positions at the Kennedy School of Government at Harvard University and at the School of Advanced International Studies at Johns Hopkins University. His latest book focuses on the broader issue of terrorism inside the United States; how individuals are radicalized, the methods used to identify terrorist plots and the instances when state institutions have failed to curb them. Bergen draws a parallel in the opening chapter, as Hamza Khan and his siblings planned to embark on a journey to the ‘perfect Islamic state’. He observes that they were not unlike Americans in the 1930’s who had thronged to Spain to show support to the antifascists fighting Franco.